2005
DOI: 10.1163/1568562053654121
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene oxide)-b-poly(N-isopropylacrylamide) nanoparticles with cross-linked cores as drug carriers

Abstract: Micelle-like nanoparticles that could be used as drug delivery carriers were developed. The unique feature of these nanoparticles was that the core of poly(ethylene oxide)-b-poly(Nisopropylacrylamide) (PEO-b-PNIPAAm) micelle was lightly crosslinked with a biodegradable crosslinker N,N-bis(acryloyl)cystamine (BAC). The nanoparticles were characterized by dynamic light scattering and fluorescence measurements. When the BAC was from 0.75 wt% to 0.2 wt% of the mass of NIPAAm, the diameters of the nanoparticles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Recently, Zeng and Pitt83 synthesized a new micellar vehicle using a block of polyethylene oxide, N ‐isopropyl acrylamide (NIPAAm), and polylactate ester of hydroxyl‐ethyl methacrylate (pENHL) (see Fig. 1).…”
Section: In Vitro and In Vivo Examplesmentioning
confidence: 99%
“…Recently, Zeng and Pitt83 synthesized a new micellar vehicle using a block of polyethylene oxide, N ‐isopropyl acrylamide (NIPAAm), and polylactate ester of hydroxyl‐ethyl methacrylate (pENHL) (see Fig. 1).…”
Section: In Vitro and In Vivo Examplesmentioning
confidence: 99%
“…Christine et al [25] have reported PEO blend copolymer micelles as a delivery vehicle for dihydrotestosterone. Zeng and Pitt [26] have also reported PEO blend nanoparticles with crosslinked cores as drug carrier. PEO is a good drug delivery vehicle in pharmaceutical industries [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The contents of these carriers are then released at the target site, thus reducing the negative side effects associated with systemic drug administration of free drug. Ample literature exists in which micelles are used as drug delivery carriers [37,[43][44][45][46][47][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Kwon et al studied the loading of Doxorubicin in micelles of poly(ethylene oxide)-poly(β-benzyl-L-aspartate) [52].…”
mentioning
confidence: 99%